Legal Protection of Children Involved in Crime of Terrorism - Prananta Garcia Ginting; Yasmirah Mandasari Saragih; Mhd. Azhali Siregar; Ongku Sapna Fella Hasibuan; Daniel Edward H Situmorang (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Terrorism is a crime related to humanity accompanied by serious threats that have an impact on the integrity and sovereignty of a country. In Indonesia itself, criminal acts of terrorism are a serious problem. Because in their implementation they not only involve adults but also involve children who do not know or understand anything about terrorism. Children as victims of criminal acts of terrorism really need legal protection so that these children can get their rights back. The research method used in this paper uses normative legal research methods. Meanwhile, the technique for collecting legal materials is carried out by conducting a literature study of secondary legal materials. Then, based on legal theories, it is analyzed qualitatively to obtain conclusions from the problem formulations that have been determined. This research aims to find out the process of handling children involved in criminal acts of terrorism and to find out what form of legal protection is given to children involved in criminal acts of terrorism. The results of this research indicate that the process of handling children involved in criminal acts of terrorism is carried out by implementing the Juvenile Criminal Justice System with the conceptrestorative justiceand children will receive protection from violence and discrimination, namely guaranteeing the protection of children's rights to live, grow, develop and participate optimally in accordance with human dignity.